Aeromonas veronii Infection in Commercial Freshwater Fish: A Potential Threat to Public Health - Tong Li; Sayed Haidar Abbas Raza; Bintong Yang; Yufeng Sun; Guiqin Wang; Wuwen Sun; Aidong Qian; Chunfeng Wang; Yuanhuan Kang; Xiaofeng Shan (Animals, 2020)
Aeromonas veronii is an important pathogen causing freshwater fish sepsis and ulcer syndrome. An increasing number of cases have demonstrated its significance as an aquatic zoonotic agent. The purpose of this study was to ensure the safety of freshwater products by evaluating the infection status of edible freshwater fish. In this experiment, we isolated A. veronii from several species of apparently healthy freshwater fish, including Carassius auratus, Cyprinus carpio, Ctenopharyngodon idella, and Silurus asotus. A. veronii was identified through bacterial staining, culture characteristics, and 16S rDNA gene sequence. In addition, polymerase chain reaction (PCR) was used to investigate the distribution of seven major virulence genes, including aerolysin (aer: 88.51%), cytotoxic enterotoxin (act: 71.26%), serine proteinase (ser: 54.02%), adhesin (Aha: 40.23%), phospholipase (lip: 45.98%), nuclease (exu: 51.72%), and quorum sensing-controlled virulence factor (LuxS: 59.77%). In total, 496 strains of Aeromonas were isolated, including 87 strains of A. veronii. The isolates of A. veronii were Gram-negative, rod-shaped bacteria, and the colonies are yellow on Rimler-Shotts (RS) medium and showed greater than 99% homology with A. veronii ATCC35624 according to analyses of the 16S rDNA sequence. Nearly 50% of the A. veronii isolates carried at least four or more virulence genes, 25% of the isolates carried at least five types of virulence genes, and 59.77% isolates carried the LuxS gene, and the isolates carrying more virulence genes were found to be more virulent. These results are of great significance for further improving the food safety assessment of freshwater aquatic products.